FACTOR AFFECTING STUDENTS LACK IN PARTICIPATING MBKM AT ENGLISH DEPARTMENT OF UKI TORAJA - Heny Puspita Bunga (Teaching English as a Foreign Language Overseas Journal, 2023)
MBKM is a policy that gives students the right to study three semesters outside of the study program. There are eight MBKM programs, namely teaching assistance, student fairs, internships, entrepreneurial activities, research, independent projects, humanitarian projects, and Thematic KKN. In this study, researchers used a qualitative descriptive method. . The participants in this study were students from the English study program. To collect data, researchers used interviews. Researchers used snowball sampling to select students to collect data. The results of the study finally concluded that the answers to the research questions about what were the shortcomings of students in participating in the MBKM apprenticeship program in the UKI Toraja English department, the researchers concluded that there was a lack of self-confidence, lack of information obtained by students about the MBKM program, even a lack of good public speaking make students not participate in the MBKM program